2016
DOI: 10.1007/s12013-016-0744-7
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-inflammatory Effect of Gnaphalium affine Through Inhibition of NF-κB and MAPK in Lipopolysaccharide-Stimulated RAW264.7 Cells and Analysis of Its Phytochemical Components

Abstract: Gnaphalium affine is an annual herbaceous plant that is used as a traditional medicine in some Latin American and Asian countries. However, systematic studies on its anti-inflammatory activity and signaling pathways have not yet been reported. In this study, we investigated the anti-inflammatory effect of G. affine methanol extract in lipopolysaccharide (LPS)-stimulated RAW 264.7 murine macrophage cells and fractioned the methanol extract into hexane, chloroform, ethyl acetate (EtOAc), butyl alcohol (BuOH), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Specifically, the p38 protein has been shown to be an essential factor for the cytokines secretion as well as the main enzymes during the inflammation interaction of the host (Lu et al., 2014) from which we could speculate that the PEPs displayed its key anti‐inflammatory activities through the downregulation effects of the inflammatory cytokines and some immune mediators (Jiang et al., 2017). The expression and function of Erk1/2 has been considered to be related to the activation of LPS‐induced cellular responses including the increased production of TNF‐α, NO, and IL‐6 in the immune cells (Seong, Hwang, & Kim, 2016). We could confirm that the MAPK pathway was one of the functional signal pathways for the alteration effects of WPEP and NPEP on the cell inflammation induced by LPS.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the p38 protein has been shown to be an essential factor for the cytokines secretion as well as the main enzymes during the inflammation interaction of the host (Lu et al., 2014) from which we could speculate that the PEPs displayed its key anti‐inflammatory activities through the downregulation effects of the inflammatory cytokines and some immune mediators (Jiang et al., 2017). The expression and function of Erk1/2 has been considered to be related to the activation of LPS‐induced cellular responses including the increased production of TNF‐α, NO, and IL‐6 in the immune cells (Seong, Hwang, & Kim, 2016). We could confirm that the MAPK pathway was one of the functional signal pathways for the alteration effects of WPEP and NPEP on the cell inflammation induced by LPS.…”
Section: Resultsmentioning
confidence: 99%
“…The mRNA expression levels of the cytokines TNF-α, IL-6 and IL-1β were analyzed by RT-PcR, according to previous studies (22,23). Total RNA was isolated using the RNeasy ® Plus Mini kit (Qiagen GmbH), and then cdNA was synthesized using AccuPower ® RT premix (Bioneer corporation).…”
Section: Reverse Transcription (Rt)-pcrmentioning
confidence: 99%
“…Although the promoter region of each proinflammatory cytokine is known to contain binding sites for NF-κB and downstream transcription factors of MAPKs, previous studies by our group demonstrated that extracts of natural plants exert different inhibitory effects on the production of proinflammatory cytokines as a result of differential regulation of NF-κB and MAPKs (41). Of note, the inhibition of TNF-α production was only detected when the extract inhibited NF-κB and all MAPKs, including JNK, ERK and p38 (42). In one instance, TNF-α production was not attenuated when the extract only inhibited one MAPK in addition to NF-κB (43).…”
Section: Discussionmentioning
confidence: 83%